The Influence of Corporate Social Responsibility, Profit Persistence, and Capital Structure To Earnings Response Coefficient. - Abdur Rahman Dalimunthe (Fakultas Ekonomi, Universitas Negeri Jakarta, 2016)
This study aims to examine the factors that influence the Earnings Response Coefficient on state-owned companies go public listed in Indonesia Stock Exchange. These factors are the corporate social responbility, earnings persistence, and capital structure.The study‟s population is a go-public SOEs company which is listed in Indonesia Stock Exchange within 2008-2011 period. The research sample using purposive sampling. Number of companies studied were 14 (fourteen) as samples and were taken by using purposive sampling method on state-owned companies went public within 2008-2011 period in Indonesia Stock Exchange, bringing the total observations in this research were 56 observations. Methods of data analysis use multiple linear regression analysis. Hypothesis tests using the t test and F test. These results indicate that corporate social responbility, earnings persistence, and capital structure affect the earnings response coefficient simultaneously at the state-owned company publicly traded on the Indonesia Stock Exchange listed period 2008-2011. Only the persistence of earnings are not significantly influence the earnings response coefficient. However, corporate social capital structure responbility and significant negative effect on earnings response coefficient. Keywords: corporate social responsibility, the persistence of earnings, capital structure, earnings response coefficient